SLC29A1 and SLC29A2 are human nicotinamide cell membrane transporters - Mingyang Chen; Luexiang Yuan; Binxin Chen; Hui Chang; Jun Luo; Hengbin Zhang; Zhongjian Chen; Jiao Kong; Yaodong Yi; Mengru Bai; Minlei Dong; Hui Zhou; et al. (Nature Communications)
Abstract Nicotinamide (NAM), a main precursor of NAD+, is essential for cellular fuel respiration, energy production, and other cellular processes. Transporters for other precursors of NAD+ such as nicotinic acid and nicotinamide mononucleotide (NMN) have been identified, but the cellular transporter of nicotinamide has not been elucidated. Here, we demonstrate that equilibrative nucleoside transporter 1 and 2 (ENT1 and 2, encoded by SLC29A1 and 2) drive cellular nicotinamide uptake and establish nicotinamide metabolism homeostasis. In addition, ENT1/2 exhibits a strong capacity to change the cellular metabolite composition and the transcript, especially those related to nicotinamide. We further observe that ENT1/2 regulates cellular respiration and senescence, contributing by altering the NAD+ pool level and mitochondrial status. Changes to cellular respiration, mitochondrial status and senescence by ENT1/2 knockdown are reversed by NMN supplementation. Together, ENT1 and ENT2 act as both cellular nicotinamide-level keepers and nicotinamide biological regulators through their NAM transport functions.